6(x-3)=45-3x

Simple and best practice solution for 6(x-3)=45-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-3)=45-3x equation:


Simplifying
6(x + -3) = 45 + -3x

Reorder the terms:
6(-3 + x) = 45 + -3x
(-3 * 6 + x * 6) = 45 + -3x
(-18 + 6x) = 45 + -3x

Solving
-18 + 6x = 45 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-18 + 6x + 3x = 45 + -3x + 3x

Combine like terms: 6x + 3x = 9x
-18 + 9x = 45 + -3x + 3x

Combine like terms: -3x + 3x = 0
-18 + 9x = 45 + 0
-18 + 9x = 45

Add '18' to each side of the equation.
-18 + 18 + 9x = 45 + 18

Combine like terms: -18 + 18 = 0
0 + 9x = 45 + 18
9x = 45 + 18

Combine like terms: 45 + 18 = 63
9x = 63

Divide each side by '9'.
x = 7

Simplifying
x = 7

See similar equations:

| -8x+19+10x+19=-2 | | 10(9x+9)=-80x | | 28=m+7 | | 3x+7=-81-7x | | 3x-2=70-9x | | x^2=6x-7 | | 3x-6+8x-24=6x-24+16x+8 | | (1/5)(3+3)=11 | | 4x=20-8 | | 54-6x=12x+16 | | 7+3y=5y-2 | | 2b+24=37 | | 12+24/8 | | 2b+2=37 | | 4m-7=8m+4 | | 2x^2-x-9=x+1 | | 238/z=17 | | 18/y=2 | | 11/2w+7=12 | | a(x+13)+15(x+13)= | | -1+10/3h=-16 | | 5y^3-10y^2+15y=0 | | 20p^5/2p^2 | | 0.25x=10 | | 2z-8=-1/2(3-5z) | | 1/2m-5/3=-1/2m+19/4 | | 15m^2n/3-m | | X=1,25(1+3300/220)+0,00005*3300 | | A/3=78 | | 7/2w-1=2w+5 | | X=1,25(1+2700/220)+0,00005*2700 | | X=1,25(1+1000/220)+0,00005*1000 |

Equations solver categories